Changing trade patterns, unchanging European and global governance - Jim O'Neill; Alessio Terzi (Bruegel, 2014)
The world economy is going through its biggest transformation in a relatively short space time. There have been many explanations for this phenomenon but the unprecedented scale and pace of this change and, most crucially, its implications, still seems little understood. In turn, there has been little preparation for, or adjustment to, this changing world, though if the change continues at this pace, the effectiveness of many global institutions in their current form will be threatened. We highlight the dramatic degree of the shifts taking place in world GDP and trade and include fresh projections of what world trade patterns might look like in 2020, should the trends observed over the past decade to continue. We also show the resulting shift in trade relationships for many key countries. European member states tend to have quite different trading partners' profiles, and this heterogeneity is quite likely to become more pronounced with time. This, in turn, suggests a significant challenge for the effective functioning of the euro area and weakens the original rationale of its creation. If our projections to 2020 are broadly right, then many established frameworks for the running of the world economy and its governance are not going to be fit for purpose, and will need to change. The global monetary system itself, and global organisations such as the IMF, G7, and G20 are going to have to adapt considerably if they want to remain legitimate representatives of the world order. The alternative is their relegation to irrelevance.
Keywords: 330